Biotrickling Filtration of Biogas Produced from the Wastewater Treatment Plant of a Brewery - Guerrero, Renata B. S. [UNESP]; Bevilaqua, Denise [UNESP] (American Society of Civil Engineers (ASCE), 2015)
The performance of a lab-scale biotrickling filter treating H2S from biogas produced from an upflow anaerobic sludge bed reactor of the wastewater-treatment plant of a brewery was evaluated. A sulfide-oxidizing culture obtained from the anaerobic sludge of the same upflow anaerobic sludge bed reactor was immobilized on polyurethane foam. The nitrate and nitrite (final electron acceptor) depletion on the trickling medium resulted in remarkable destabilization in the performance of the system. The optimum temperature was in the range from 31 to 42°C (removal efficiency=91.8±5.5%). At a temperature of 22°C the removal efficiency reduced to 39% [inlet load (IL)=5.3 gS-H2S m-3 h-1, empty bed residence time (EBRT)=2.9 min]. Trickling liquid velocity (TLV) of 4.4, 7.4, and 11 m h-1 did not affect the system at EBRT of 6.2 min (removal efficiency=94.2±1.3%, IL=1.86±0.18 gS m-3 h-1). A TLV effect was observed at an EBRT of 1.6 min where the removal efficiency decreased from 50.9% (4.4 m h-1) to 33.7% (7.3 m h-1).
Keywords: Anaerobic processes; Anaerobic sludge; Biodesulfurization; Biotrickling filter; Brewery; Open-pore polyurethane foam